Mitigation of salinity stress in cucumber seedlings by exogenous hydrogen sulfide - Turan, Metin; Ekinci, Melek; Kul, Raziye; Boynueyri, Fatma G.; Yildirim, Ertan (Journal of plant research, 2022)
This research hypothesized that tolerance of cucumber seedlings to salinity stress could be increased by hydrogen sulfide (H 2 S) treatments. In pot experiments, the cucumber seedlings were exposed to three levels of salt stress (0, 50 and 100 mM NaCl), and NaHS as H 2 S donor was foliar applied to the cucumber seedlings at five different doses (0, 25, 50, 75 and 100 µM). The effects of the treatments on cucumber seedlings were tested with plant growth properties as well as physiological and biochemical analyses. As the salinity level increased, plant growth properties and chlorophyll reading value (SPAD) decreased. However, H 2 S treatments significantly mitigated the impact of salinity. Salt stress elevated the membrane permeability (MP) and decreased the leaf relative water content (LRWC). H 2 S applied leaves had lower MP and higher LRWC than non-H 2 S applied leaves. On the other hand, photosynthetic properties (net photosynthetic rate, stomatal conductance, transpiration rate and intercellular CO 2 concentration) of the seedlings under salt stress conditions were decreased but this decrease was considerably relieved by H 2 S treatment. The K/Na and Ca/Na ratios under salt stress conditions were higher in H 2 S-applied plants than in non-applied plants. Furthermore, antioxidant enzyme activity [(catalase (CAT), peroxidase (POD) and superoxide dismutase (SOD)] and hydrogen peroxide (H 2 O 2 ), malondialdehyde (MDA), proline, and sucrose concentration in the leaves increased with salinity stress whereas they were reduced with H 2 S treatments under salt stress. Mitigation of salt stress damage in cucumber using H 2 S treatment can be expounded via modulation of enzyme activity, nutrient content, reactive oxygen species (ROS) formation, and osmolytes accumulation.